Pengaruh Video Animasi tentang Early Chilhood Caries (ECC) terhadap Tingkat Pengetahuan Orang Tua Balita - Rusdiani, Verdina; Nurnaningsih, Hera; Ningrum, Nining; Octaviana, Devy (Jurnal Terapi Gigi dan Mulut, 2025)
Early Childhood Caries (ECC) is a prevalent oral health problem in early childhood, often stemming from inadequate parental knowledge about its causes and prevention. Animation videos have proven to be effective in knowledge enhancement. This study aimed to evaluate the influence of an animation video on ECC on the knowledge level of parents of toddlers within the working area of Puskesmas Nambo, Bandung Regency. A pre-experimental study employing a One Group Pretest-Posttest Design was conducted on 56 parents of toddlers diagnosed with ECC in the Puskesmas Nambo service area. This research will be carried out in January 2025. Knowledge levels were assessed using pre- and post-test questionnaires. The study revealed that the majority of parents exhibited a moderate level of knowledge regarding ECC before receiving the animation video education. Following exposure to the video, a significant increase in knowledge levels was observed, with the majority of parents achieving a good level of understanding. The Wilcoxon test demonstrated a significant difference (p < 0.05) between the pre-test and post-test scores, indicating the effectiveness of the animation video in raising parental knowledge about ECC. Animation videos demonstrate a positive impact on increasing the knowledge of parents of toddlers regarding ECC. The study recommends the adoption of animation videos as an educational tool within various healthcare facilities and public platforms.